Prototype of We Share Blood an App for Searching Blood Donation based on Android Platform - ., Suryatiningsih; Siradj, Yahdi; Hakim Cahyono, Rul (International Journal of Engineering and Technology, 2019)
The gap between the availability of blood stock in the blood bank and the need for blood in Indonesia is more than 50%. In the process, the patients who did not receive blood donor from the blood bank, to find the potential blood donors the patient usually sends a broadcast message which is this way is out of focus. Related to this, we proposed an alternative way to look for potential blood donors which geographically located around the patient by adopting Location Based Services (LBS).The methodology used in this research is the prototype method because this research focuses on the fast interaction between the user and the prototype application. This paper presents a design of a mobile app prototype for finding potential blood donors with match blood type information combined with its geographic location using LBS technology based on Android platform.Â